Miss Fisher's murder mysteries. [videorecording (DVD)] Series 2 - Davis, Essie; Page, Nathan, 1973-; Johnstone-Burt, Hugo; Greenwood, Kerry ([Publisher not identified], 2013)
Armed with a razor-sharp wit, Miss. Fisher investigates crimes in opulent 1920s Australia. Sharply written and gorgeously costumed, these episodes are sure to charm fans of costume dramas and mysteries alike.